Inti sari karya klasik - Rogayah A. Hamid, 1954-; Etty Zalita Zakaria (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2007)
Malay folk literature from Malaysia, Indonesia, and Brunei; collection of abstracts
In Malay, and some texts in Indonesian
Keywords: Folk literature, Malay; Malay literature; Malay poetry